Design for social change and design education: Social challenges versus teacher-centred pedagogies. (28th July 2017) - Souleles, Nicos
Abstract: Increasingly, various design-related processes are employed to address social issues. Design for social change entails the adoption of a variety of strategies that at their core are human-centred. There is an expectation that design education should cater for the competencies that will allow graduates to deal successfully with the challenge of design for social change. However, teacher-centered instructional approaches neglect end-users; they are not human-centered. This position paper argues that learner-centered instructional approaches that emphasise the use for example of ethnographic studies, action research and empathy, are better equipped to cater for design for social change. They tend to adopt an evidence-based approach that is human-centered. If design education is to contribute towards social change, then it needs to rid itself of the master-apprentice instructional model. Instead, it should adopt user-centred and evidence-based approaches, and thus move closer strategies that can facilitate a variety of social interventions.